Blood-brain barrier breakdown during cerebral malaria: Suicide or murder? - Pino, Paco; Taoufiq, Zacharie; Nitcheu, Josiane; Vouldoukis, Ioanis; Mazier, Dominique (Thrombosis and Haemostasis, 2005)
Cerebral malaria, one of the most serious complicatiof ons Plasmodium falciparum infection, is characterized by the sequestration of parasitized red blood cells (PRBCs) in cerebral microvascular beds. The precise mechanisms involved in the onset of neuropathology remain unknown, but parasite sequestration in the brain, metabolic disturbances, and host immune responses all play a role. Sequestration of PRBCs is mediated by different endothelial cell surface receptors, mainly ICAM-1 and CD36. In vitro studies demonstrated that PRBC adhesion to endothelial cells induces over-expression of various adhesion molecules including ICAM-1, expression of iNOS, oxidative stress and finally apoptosis in endothelial cells. In vivo studies, in humans and in mice models of cerebral malaria brought striking evidence of the implication of brain infiltrating cytotoxic effector CD8T lymphocytes in the development of murine cerebral malaria pathogenesis. These cells probably act by direct cytotoxicity against endothelial cells. Cytotoxicity and apoptosis potentially lead blood-brain-barrier disruption and could contribute to the development of cerebral malaria. We propose a key role for endothelial cells in the pathogenesis of cerebral malaria, both by suicide / apoptosis, and / or by murder / cytotoxicity.
Keywords: Cerebral malaria; adhesion; apoptosis; cytotoxicity; endothelialcell